Buying Interest is Also Influenced by Price - Purwanto Fajar Trisno; Ahmadijaya Ghiffari; Owen Michael (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The development of cafe business has spread in several big cities in Indonesia, one of which is Semarang city. In this city, the number of cafes that sell speciality coffee is growing and increasing up to five times. The growth of coffee shop in Semarang has appealed to coffee shop entrepreneurs in Semarang, such as Strada Coffee, Kelas Kopi, Antara Kata, Black Bone Coffee, and Peacook Coffee.This increasing number of coffee shops also triggers the growing competition among them. A coffee shop crowded with coffee lovers is a coffee shop with high quality product and affordable price, and can be accepted by all coffee lovers. Some coffee shops in Semarang are starting to sell two kinds of coffee based on its presentation, which are manual brew and espresso base. However, not all coffee shops in Semarang have manual brew coffee as their product since some people in Semarang do not understand well the brewing system of manual brew coffee